Limitations on Hybrid WDM/OTDM Multicast Overlay System Imposed by Nonlinear Polarization Effect and its Mitigation - Sukhbir Singh; Surinder Singh (IEEE Photonics Journal)
This paper investigates the nonlinear polarization effect of 120-Gbps polarization and subcarrier multiplexed unicast signal and 40-Gbps multicast signal on transmission performance of hybrid WDM/OTDM multicast overlay system. The interaction between Kerr nonlinearity and polarization mode dispersion (PMD) induced nonlinear cross polarization modulation (XPolM) effect can significant limits the transmission performance of hybrid WDM/OTDM multicast overlay system. The effect of signal input power, extinction ratio, PMD, and differential group delay is studied in multicast enable and disable mode. Also, a mitigation technique of nonlinear polarization effect is introduced by use of group delay compensator, judicious addition of some PMD, and inline pre-DCF in the transmission channel. It is also found that the amplitude to phase interaction between multicast and unicast signal transmission can be suppressed by controlling the loss of orthogonality.